Confined-space synthesis of hierarchical SnO2 nanorods assembled by ultrasmall nanocrystals for energy storage. Issue 85 (30th August 2016) - Wang, Menghu; Ping, Hang; Xie, Hao; Chen, Baoli; Yan, Min; Fang, Weijian; Fu, Zhengyi
Abstract : The cell display based approach synthesizes carbon coated hierarchical nanostructured SnO2, exhibiting good lithium storage properties. Abstract : A genetically modified bacterial surface not only serves as a confined environment for controlling the monodispersity of particle size, but also provides a carbon source in situ . The carbon coated SnO2 composite exhibits good lithium storage properties as an anode electrode, which are due to the ultrasmall size of the particles, the carbon coating and mesoporous structure.